Formulasi Obat Kumur Minyak Atsiri Sereh Wangi (Cymbopogon nardus (L.) Rendle) dan Uji Aktivitas Antibakteri terhadap Streptococcus mutans - Marisa Tamara Sari; Yelfi Anwar; Andrianopsyah Mas Jaya Putra (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2023)
Mouthwash is a liquid, aqueous composition that is primarily used to treat oral conditions, as well as maintain oral health. The purpose of this study was to prove the antibacterial efficacy of citronella essential oil against Streptococcus mutans bacteria made in mouthwash formulations. Citronella essential oil was analyzed using GC-MS and then formulated into a mouthwash with concentrations of 1.5%, 3% and 4.5% at cold temperatures (2-8°C) and room temperature (20-25°C).The test results were evaluated, and analyzed using One Way ANOVA and Post Hoc Tukey. The GC-MS results showed that 3 main compounds were detected, namely Citronellol (11.69%), Geraniol (15.59%), and Citronellal (24.57%). The mouthwash formulation did not show any organoleptic change in physical preparation, was homogeneous, had a pH range of 4.91-5.18 at cold temperature and pH 5.02-5.23 at room temperature, had a viscosity consistency that met the standard of 0.8 -1 at cold temperature and room temperature, and no separation was found, such as the presence of precipitate in each treatment. Formula 3 is considered to have medium inhibition compared to formulas 1 and 2 with an average inhibition power at cold temperature formula 6.73 while at room temperature formula 7.35. Briefly, the formulation is stable both at cold temperature (2-8°C) and room temperature (20-25°C) with moderate inhibition at a concentration of 4.5%.